KRITIK TERHADAP PEMIKIRAN RASYID RIDHA TENTANG HADIS IMAM MAHDI - Rizal, Mutaqin Samsul; Rizal, Purnama Faturohman (Tahdis: Jurnal Kajian Ilmu Al-Hadis, 2022)
The discussion about Imam Mahdi its seem as endless among the scholars, both mutaqadimin and muta’akhirin ulama. Likewise among hadith researchers, there are always disagreements about the authenticity of Imam Mahdi’s traditions. Among the scholars who reject the authenticity of Imam Mahdi’s hadith is Rashid Rida, he said that the hadith about Imam Mahdi is contradictory, dhaif, and contain many israiliyat. This article aims to find out Rasyid Rida’s views on the hadiths of al-Mahdi and how to answer this opinion. The research method that can facilitate this analysis is the Content Analysis method with a qualitative approach. Seeing Rasyid Rida’s opinion regarding the hadith of al-Mahdi as stated in al-Manar’s interpretation, then the sanad criticism was carried out consisting of Takhrij hadith, I’tibar, making a sanad scheme. There are two traditions from Ibn Majah’s narrative commented on by Rasyid Ridha, with that comment in the sanad of the hadith there is rawi dha’if and considered tasyayu ’and there are narrators who are considered mudallis. This opinion of Rasyid Rida violates the ijma ’of the scholars who state that the hadiths of al-Mahdi are authentic and even reach the degree of meaningful mutual worry. The scholars have agreed that the hadiths of al-Mahdi are authentic and reach the degree of mutual concern, people who deny al-Mahdi are seen as Qur’aniyyun and deny Allah’s uluhiyah.